Atom Transfer Radical Polymerization of Styrene and Acrylates: Effects of Catalyst, Ligand, Solvent, and Initiator - Ullah, M. W.; Haraguchi, N.; Ali, M. A.; Alam, M. R.; Mahiuddin, M.; Ahamed, S. K. (Journal of Scientific Research, 2021)
Well-defined polystyrenes were successfully prepared by the CuX/(dN)bpy or CuX/ PMDETA catalyzed atom transfer radical polymerization of styrene using 1-phenylethyl bromide (1-PEBr) or benzyl bromide (BnBr) as initiators. We found that the CuX/PMDETA catalyzed ATRP of styrene proceeded faster than CuX/(dN)bpy catalyzed counterpart in bulk, diphenyl ether (DPE) and anisole. Using CuX/(dN)bpy catalyst, well-defined polystyrenes were obtained with good chain-end functionalities and low polydispersity (Mw/Mn <1.5) compared to CuX/PMDETA catalyst. The CuBr/PMDETA catalyzed ATRP of n-butyl acrylate (nBA), n-butyl methacrylate (nBMA), and tert-butyl methacrylate (tBMA) were also proceeded in a controlled manner. The molecular structure and molecular weight of polymers were determined by proton nuclear magnetic resonance (1H NMR) spectroscopy and size exclusion chromatography (SEC), respectively.